Keakhlian Baru Akuntan pada Era Digital - Elizabeth Tiur Manurung; Monica Paramita Ratna Putri; Fransisca Elza (Seminar Nasional Penelitian dan Abdimas, 2023)
The revolution of 4.0 industry has changed the way of doing business to be electronically based. This also emerge a revolution for the Accountants, a new requirement and new competencies that different from previous one. The rapid advancement in information technology has reshaped the job for Accountants which is now focused on in-depth digital and analytical aspects digital operating systems, network technology, computer programming, authentication techniques, security techniques (firewalls), and suitable device in accordance with modern technology at that time. This study aims to uncover what new skills are needed by nowadays Accountants, and how to develop potential Accounting Students and Accountants Candidate in digital era. The study has been conducted with quantitative method, using data processing from questionnaire to 180 respondents from senior high school students; and hypothetical deductive method from 30 students answers regarding the a proposed hypothesis of digital audit studies. The result shows that all senior high school students are very interested of gaining new knowledge of new competencies of Accountants in digital era. In addition, Accounting Department of UNPAR also provided sufficient knowledge for alumni who wish to career in digital auditing